Al-hawājizu bayna Al-bahrayni fi Al- Qur’āni ‘inda Zaghlul An-Najjaar (الحواجز بين البحرين في القرآن عند زغلول النجار) - Dinni Nazhifah; Gilang Rizki Aji Putra (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The sea is one form of the Earth's surface that its components are made of liquid. Before the 20th century human beings simply know that all liquid when at the combine, it will become one, because the liquid has the nature of blending, but lately in the 20th century something strange was discovered, which was not mixed with seawater, one example of which was in the Straits of Giblatar. which at that time the human record was far from science, but in the Qur'an there was little explanation of the matter. Departing from the background above, the writer therefore tries to uncover and examine about a barrier that is in the quran. The author uses a literature study that uses the Zaghlul Annajar book as a primary source and books written by other people as secondary sources. The author also uses a science approach to be able to uncover verses related to science. The results achieved by the research using the method discussed then the water barrier contained in the quran is a front of water or it can be called the